A novel method of thermo-mechanical coupled analysis based on the unified description. (April 2019) - Cui, Ya-Qi; Yu, Zu-Qing; Lan, Peng
Highlights: A novel method of the thermo-mechanical coupled analysis which is based on the unified description is proposed. The heat transfer is integrated with the continuum mechanics via the unified description of the displacement and the temperature field. The thermal deformation and deformation heat are introduced for the bidirectional coupling of the displacement and the temperature field. The energy (including internal energy and mechanical energy) conservation property and the irreversible transformation between different forms of energy within the thermo-mechanical coupled system are depicted. The generalized-α method is used to solve the dynamic equations and the heat transfer equations synchronously which are derived based on a unified system nodal coordinates. Abstract: A novel method of the thermo-mechanical coupled analysis which is based on the unified description is proposed. In the traditional methods, the displacement and the temperature field were solved in different meshes, which resulted in a series of data mapping problems in joint simulation. In order to integrate the heat transfer with the continuum mechanics, a unified description for the displacement and the temperature field is proposed. Based on this idea, a thermal integrated Absolute Nodal Coordinate Formulation fully parameterized beam element is constructed. The dynamic equations and the heat transfer equations are established using a unified element mesh. Thermal deformation and deformation heating caused by material viscosity are both introduced for describing the bidirectional coupling effect of the two physical fields. Accordingly, the energy conservation property and the transformation between different forms of energy within the thermo-mechanical coupled system could be depicted. A scheme based on the generalized-α method is presented to solve the two sets of governing equations synchronously. Several numerical examples are given to demonstrate the feasibility of the presented method.